Transmembrane Domain Interactions Control Biological Functions of Neuropilin-1 - Roth, Lise (The American Society for Cell Biology, 2008)
Neuropilin-1 (NRP1) is a transmembrane receptor playing a pivotal role in the control of semaphorins and VEGF signaling pathways. The exact mechanism controlling semaphorin receptor complex formation is unknown. A structural analysis and modeling of NRP1 revealed a putative dimerization GxxxG motif potentially important for NRP1 dimerization and oligomerization. Our data show that this motif mediates the dimerization of the transmembrane domain of NRP1 as demonstrated by a dimerization assay (ToxLuc assay) performed in natural membrane and FRET analysis. A synthetic peptide derived from the transmembrane segment of NRP1 abolished the inhibitory effect of Sema3A. This effect depends on the capacity of the peptide to interfere with NRP1 dimerization and the formation of oligomeric complexes. Mutation of the GxxxG dimerization motif in the transmembrane domain of NRP1 confirmed its biological importance for Sema3A signaling. Overall, our results shed light on an essential step required for semaphorin signaling and provide novel evidence for the crucial role of transmembrane domain of bitopic protein containing GxxxG motif in the formation of receptor complexes that are a prerequisite for cell signaling.